Pengaruh Return on Assets (ROA), Return on Equity (ROE) dan Net Profit Margin (NPM) terhadap Pertumbuhan Laba Perusahaan Makanan dan Minuman yang Tercatat di Bursa Efek Indonesia Tahun 2021-2025 - Erlina Devinta; Sri Laksmi Pardanawati; Indra Lila Kusuma (YASIN, 2026)
Global economic fluctuations and declining public purchasing power in the post-pandemic period have become challenges for the food and beverage industry in maintaining consistent net profit growth. This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on the profit growth of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. This study used a quantitative approach with a sample of 21 companies selected through purposive sampling, resulting in 105 observational data. The data were analyzed using classical assumption tests and multiple linear regression. The results show that ROA, ROE, and NPM simultaneously had a significant effect on profit growth (Fcount = 45.141 > Ftable = 2.69; p < 0.05). Partially, ROA had a positive and significant effect on profit growth (t = 3.284; p = 0.001), and ROE also had a positive and significant effect (t = 5.325; p = 0.000). Conversely, NPM had no significant effect on profit growth (t = -1.505; p = 0.135). The Adjusted R Square value of 0.560 indicates that ROA, ROE, and NPM were able to explain 56% of the variation in profit growth, while the remaining 44% was influenced by other factors outside the research model. The conclusion of this study emphasizes that profit growth in the food and beverage sector is determined more by the efficiency of asset management and the effectiveness of optimizing equity capital than by the net profit margin from sales. The implications of this study indicate the importance of improving the efficiency of fixed asset utilization, strengthening a healthy capital structure, and developing more economical product innovation for company management, as well as using ROA and ROE as the main fundamental indicators for investors in making investment decisions.